Analisis Manajemen Risiko Kecelakaan Kerja Pada Mesin Automatic Bar Bending dengan Metode Hazard Identification, Risk Assessment And Determining Control (HIRADC) Pada PT Faza Jaya Pratama - Muhammad Agung, Andi; Pangastuti, Nova; Parningotan , Sepriandi (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Work accidents in the construction industry are often related to the operation of machinery, including the complex Automatic Bar Bending machine. This study aims to analyze the risk management of work accidents on Automatic Bar Bending machines using the Hazard Identification, Risk Assessment and Determining Control (HIRADC) approach at PT Faza Jaya Pratama. The research method includes hazard identification, risk assessment, and determination of effective controls to reduce the risk of accidents. The results showed that the Automatic Bar Bending machine has several potential hazards that can result in serious accidents if not handled appropriately. The risk evaluation provided a deeper understanding of the level of risk associated with the machine operation, while the implementation of appropriate controls was able to significantly reduce the risk. The implication of these findings is the need for the implementation of a comprehensive risk management strategy to improve occupational safety and health in the construction industry work environment.